Physical factors affecting the production of organic solvent-tolerant protease by Pseudomonas aeruginosa strain K - Raja Abdul Rahman, Raja Noor Zaliha; Lee, Poh Geok; Basri, Mahiran; Salleh, Abu Bakar (Elsevier, 2005)
The physical factors affecting the production of an organic solvent-tolerant protease from Pseudomonas aeruginosa strain K was investigated. Growth and protease production were detected from 37 to 45 °C with 37 °C being the optimum temperature for P. aeruginosa. Maximum enzyme activity was achieved at static conditions with 4.0% (v/v) inoculum. Shifting the culture from stationary to shaking condition decreased the protease production (6.0–10.0% v/v). Extracellular organic solvent-tolerant protease was detected over a broad pH range from 6.0 to 9.0. However, the highest yield of protease was observed at pH 7.0. Neutral media increased the protease production compared to acidic or alkaline media.